Necrotic Wound Caused by Jararaca (Bothrops jararaca) in a Dog - Hyperbaric Oxygen Therapy (HBTO) - Sakata, Stella Helena [UNESP]; Gallina, Marina Frazatti [UNESP]; Mizobe, Thamires; Pereira, Guilherme Cirino Coelho [UNESP]; de Almeida, Karina Calixto [UNESP]; Zadra, Vivian Ferreira; Cramer, Claudia Tozato [UNESP]; Dos Santos, Ivan Felismino Charas [UNESP] (Universidade Federal do Rio Grande do Sul, 2022)
Background: Snakebites are the main responsible for envenoming in dogs and the bothropic venom remains the most common in Brazil, which can induce a necrotic skin wound. Hyperbaric oxygen therapy (HBOT) use 100% oxygen under high pressure and used to treat different wounds in human patients. To the authors' knowledge, no reports regarding to use the HBOT in skin wound caused by snakebite (Bothrops jararaca) are present in the literature. The present clinical case aimed to describe the use of HBOT for the treatment of an extensive necrotic wound caused by jararaca snakebite in a dog. Case: A neutered 8-year-old mixed-breed dog, weighing 12 kg, was admitted with a 7-day history of extensive necrotic wound was identified in the face and neck causing by a snakebite, and no sign of pain. The procedure of HBOT (single sessions of 1.5 ATM, 45 min, repeated every 48 h, up to 12 sessions) was decided, and the complete blood cells, alanine aminotransferase, creatinine, creatine kinase, prothrombin time, activated partial thromboplastin time, wound clinical evaluation were measured at the following time-points: 2nd, 5th, 10th, and 12th sessions. At the 5th session was identified leukopenia, neutropenia and lymphopenia. Wound re-epithelialization was initiated after the 5th session, and the complete epithelialization was identified at the 12th session of HBOT. During the HBOT no side effects were identified. Three months after the HBOT finished, the animal returned to the clinic and the clinical status evolved positively, and the wound was completed healed. Discussion: This report described the treatment of an extensive necrotic skin wound caused by snakebite (Bothrops jararaca) in an 8-year-old, neutered, mixed-breed dog using the HBOT. The wound healing was achieved after 12 sessions, similar to the literature, which reported a ranging from 1 to 12 sessions. The HBOT protocol used in this case was similar as reported for human patients with chronic wounds due to the lack of HBOT protocols for animals. No reports regarding the use of HBOT for treat necrotic wound caused by snakebite was described in the literature, and to the authors' knowledge, this is the first report in Brazil describing the use of HBOT in dogs. On the other hand, dogs with surgically induced skin wounds and treated with daily session of HBOT using the treatment protocol of 1.7 ATM (30 min) and 2.0 ATM (40 min) up to 7th day of treatment did not show significant results on healing [9]. This fact was associated with the HBOT achievement in the proliferative and remodeling phases of the healing process. The high intensity of HBOT was between the 5th and 10th session since the wound showed a higher area decrease rate and consequently increase of wound contraction. This period was corresponding to the 10th and 20th day of the healing process, which can be identified angiogenic activity, re-epithelialization, and collagen maturation. The decrease in PVC has been associated with the anticoagulant and/or hemorrhagic activity caused by the venom, and leukopenia, neutropenia and lymphopenia was related with possible bone marrow exhaustion. Single sessions of HBOT (1.5 ATM, 45 min, and repeat each 48 h, up to 12 session) induces healing of necrotic wound caused by snakebite (Bothrops jararaca) in an 8-year-old, neutered, mixed-breed dog without any side effects.
Keywords: Dog; Healing; Hyperbaric chamber; Skin wound; Snake